Efficacy and safety of tirofiban injection with intracranial stenting in early reocclusion due to intracranial atherosclerosis - Yun Ho Noh; Ji Young Lee; Seok Mann Yoon; Yu Jin Ha; Jaewoo Chung; Jung Ho Ko; Dong Seong Shin; Jae-Min Ahn; Hyuk Jin Oh; Jai-Joon Shim; Man Ryul Lee; Jae Sang Oh (Interdisciplinary Neurosurgery, 2022)
Objective: We aimed to develop an optimal protocol for failed mechanical thrombectomy (MT) in cases of emergent large vessel occlusion (ELVO) with intracranial atherosclerosis (ICAS). Methods: A total of 117 patients without underlying heart disease who were not taking antiplatelet drugs had early reocclusion during MT for ELVO due to ICAS. They were divided into the following 3 groups according to rescue treatment methods: 1) Combined intravenous (IV) + intra-arterial (IA) tirofiban group (n = 48), emergent percutaneous transluminal angioplasty (PTA) and intracranial stenting (ICS) followed by IA injection of tirofiban and a continuous IV tirofiban infusion for 8 h; 2) IA tirofiban group (n = 33), only IA 0.5–1.0 mg tirofiban infusion for 5 min regardless of PTA or ICS; and 3) no tirofiban group (n = 36), no tirofiban injection regardless of PTA or ICS. Results: ICS was more frequently performed in the combined IV + IA tirofiban group than in the IA tirofiban group (100% vs 46%, p < 0.05). The proportion of m-TICI grades 2b and 3 (93.8% vs. 63.6%, p < 0.05), especially the proportion of m-TICI grade 3 (81.3% vs. 36.4%, p < 0.05), was higher in the combined IV + IA tirofiban group than in the IA tirofiban group. The rate of postoperative intracranial hemorrhage was not significantly different among the three groups. The rate of modified Rankin scale scores of 0–2 at 3 months after MT was highest in the combined IV + IA tirofiban group (63%), followed by the IA tirofiban (46%) and no tirofiban groups (8%, p < 0.05). Conclusion: ICS with IA and continuous IV tirofiban injections for 8 h is an effective and safe protocol for failed MT in patients with ELVO with ICAS.